Therapeutic Plasma Exchange as Adjuvant Rescue Therapy for Weil’s Disease-Associated Acute Liver Failure in a Hemodialysis-Dependent Patient: A Case Report - Ardana Tri Arianto; Aura Ihsaniar; Lichte Christian Purbono (HM Publisher, 2026)
Background: Weil’s disease, the severe form of leptospirosis, manifests as a triad of jaundice, renal failure, and hemorrhage. In patients with pre-existing end-stage renal disease (ESRD), the management of superimposed acute liver failure (ALF) is exceptionally challenging due to altered pharmacokinetics, fluid intolerance, and the inability of standard hemodialysis to clear protein-bound hepatic toxins. Case presentation: We present a 32-year-old anuric male with ESRD on maintenance hemodialysis who presented with fever, jaundice, and altered mental status following floodwater exposure. He developed severe metabolic encephalopathy (GCS E2V2M4), profound coagulopathy (INR 6.04), and hyperbilirubinemia (Total Bilirubin 18.31 mg/dL). Following the failure of broad-spectrum antibiotics and sustained low-efficiency dialysis (SLED) to halt clinical deterioration, two sessions of therapeutic plasma exchange (TPE) were initiated as salvage therapy. The intervention utilized 100% fresh frozen plasma (FFP) replacement to address hemostatic failure. TPE resulted in rapid biochemical clearance and clinical stabilization. Post-intervention, the INR decreased from 6.04 to 1.57 (74% reduction), Total bilirubin declined from 18.31 to 5.57 mg/dL (69.5% reduction), and platelet counts recovered from 45,000 to 142,000/µL. Neurological status normalized (GCS 15) within 48 hours of the second session. Conclusion: TPE served as an effective bridge to recovery by clearing albumin-bound toxins and restoring coagulation factors in a high-risk patient where standard renal replacement was insufficient.